Puppets theater group health with art : nursing proposal for education in health - Sousa, Rosilea Alves de; Victor, Janaína Fonseca (Rev Rene, 2007)
This research intends to report an experience of forming a theatre group with puppets Art with health developed by nurses and nursing technicians at a University Hospital in Fortaleza, Ceará. The implementation of the puppets theatre contemplated four stages: sensibilization, concretization, integration and presentation. The puppets were made with felt, accessories, also with ethylene-vinyl acetate (E.V.A) and card board. The articulated and dismountable scenery was built with wood (1,60m X 2,50m). The group experience allowed people that were engaged to glimpse new ways of caring through actions supported by scientific knowledge, but also empowered by other aspects of human totality such as joy and entertainment. The theatre group made possible the realization of nursing actions aiming the promotion of health in a different way.